An Integrated Process of Design Thinking for Sustainability of Indian Start-ups - Supriya Kapai, Rahul Hiremath, Pranita Ranade (International Journal of Advanced Science and Technology, 2020)
Start-ups can play an important role in economic growth of any country. These produce more jobs that lead to more employment, and more employment helps in contributing to an improved economy. Start-ups can also contribute to economic strength and dynamism of the economy by motivating innovation and introducing competition. Start-ups are always risky propositions but potential investors have several approaches to determining their value. Indian start-ups face many hurdles in implementation of Sustainable development goals; hence this creates a good opportunity for integrated design thinking approaches to sustainability of economic and entity goals. During the Start-up development, their team is expected to completely identify and understand their customer’s needs, but it is challenged by geographic limitations, restricted project schedule, or less budget. Design Thinking is a strategic approach that stimulates the understanding of consumer’s needs considering what is technically and economically workable. This paper aims to examine potential promoters and limitations of integrated design thinking with a focus to sustainable establishment and running of start-ups in India. The study will further develop a model for integrated design thinking strategy that could enhance; optimal result attainment from the circular economy initiatives and strategic sustainability achievements.